The self‐secondary crater population of the Hokusai crater on Mercury - Zhiyong Xiao; Nils C. Prieur; Stephanie C. Werner (Geophysical Research Letters)
Abstract Whether or not self‐secondaries dominate small crater populations on continuous ejecta deposits and floors of fresh impact craters has long been a controversy. This issue potentially affects the age determination technique using crater statistics. Here the self‐secondary crater population on the continuous ejecta deposits of the Hokusai crater on Mercury is unambiguously recognized. Superposition relationships show that this population was emplaced after both the ballistic sedimentation of excavation flows and the subsequent veneering of impact melt, but it predated the settlement and solidification of melt pools on the crater floor. Fragments that formed self‐secondaries were launched via impact spallation with large angles. Complex craters on the Moon, Mercury, and Mars probably all have formed self‐secondaries populations. Dating young craters using crater statistics on their continuous ejecta deposits can be misleading. Impact melt pools are less affected by self‐secondaries. Overprint by subsequent crater populations with time reduces the predominance of self‐secondaries.